The impact of thrombo‐inflammation on the cerebral microcirculation. (21st March 2021) - Ansari, Junaid; Gavins, Felicity N. E.
Abstract: The intertwined processes of thrombosis and inflammation (termed "thrombo‐inflammation") are significant drivers of cerebrovascular diseases, and as such, they represent prime targets for drug discovery programs focusing on treatment and management of cerebrovascular diseases. Most cerebrovascular events result from chronic systemic microcirculatory dysfunction due to underlying conditions, for example, hypertension, diabetes mellitus, coronary artery disease, dyslipidemia, and sickle cell disease. Immune cells especially neutrophils play a critical role in the onset and maintenance of neuroinflammatory responses in the microcirculation. Neutrophils have the ability to drive both inflammatory and anti‐inflammatory/pro‐resolution effects depending on the underlying vascular state (physiological vs. pathological). In this article, we highlight the pathophysiological role of neutrophils in stroke and discuss ongoing pharmacotherapeutic strategies that are focused on identifying potential therapeutic targets for enhancing neuroprotection, mitigating inflammatory pathways, and enabling resolution.